Salidroside Alleviates Cartilage Degeneration Through NF-κB Pathway in Osteoarthritis Rats - Gao H; Peng L; Li C; Ji Q; Li P (Dove Medical Press, 2020)
Hui Gao,1,* Lu Peng,2,* Chao Li,1 Qinlong Ji,1 Ping Li3 1Department of Orthopaedics, Tinglin Hospital, Shanghai 201505, People’s Republic of China; 2Department of Orthopaedics, Hospital of Traditional Chinese Medicine, E’dong Healthcare Group, Huangshi 435000, People’s Republic of China; 3Department of Rehabilitation, Hanchuan People’s Hospital, Hanchuan, 431600, People’s Republic of China*These authors contributed equally to this workCorrespondence: Ping LiDepartment of Rehabilitation, Hanchuan People’s Hospital, NO.1 Renmin Avenue, Hanchuan City, Hubei Province, People’s Republic of ChinaTel +86-18371202625Email kezzajps2jf@sina.comIntroduction: Osteoarthritis (OA) is the most common disease, which seriously affects the daily life of the elderly. Currently, no traditional or drug therapy has been shown to explicitly block the progression of OA. Salidroside (Sal) is a bioactive component of Rhodiola rosea, which has many beneficial effects on human health. However, the role and mechanism of Sal in OA have not been reported.Methods: We established an anterior cruciate ligament transection (ACLT)-induced OA Rat model. The rats were divided into five groups (n = 10): Control group; ACLT group; ACLT + Sal (12.5 mg/kg) group; ACLT + Sal (25 mg/kg) group; ACLT + Sal (50 mg/kg) group.Results: The study showed that Sal could significantly promote the proliferation of chondrocytes in OA rats induced by ACLT and restore the histological alteration of cartilage. Besides, Sal upregulated the levels of Collagen II and Aggrecan, and downregulated the level of MMP-13. Furthermore, Sal could reduce the number of CD4+IL-17+ cells and decrease the levels of IL-17, IKBα and p65, while elevating the number of CD4+IL-10+ cells and the level of IL-10. The decrease of IL-17 further inhibited the dissociation of IKBα to p65, thus reducing the release of TNF-α and VCAM-1. Taken together, Sal alleviates cartilage degeneration through promoting chondrocytes proliferation, inhibiting collagen fibrosis, and regulating inflammation and immune responses via NF-κB pathway in ACLT-induced OA Rats.Discussion: Collectively, our study investigates the role and mechanism of Sal in OA, which lays a foundation for the application of Sal in OA.Keywords: osteoarthritis, salidroside, cartilage degeneration, collagen fibrosis, inflammation, immune responses, NF-κB